2016
DOI: 10.4174/astr.2016.90.6.297
|View full text |Cite
|
Sign up to set email alerts
|

An online questionnaire survey on preferred timing for the diagnosis and management of thyroid carcinoma in general population in Korea

Abstract: PurposeAn optimal timing for diagnosis and management of papillary thyroid microcarcinoma (PTMC) has become the subject for much controversy. The aim of the present study is to analyze people's preference in Korea for timing of diagnosis and management of PTMC using an online questionnaire.MethodsThe questionnaire consists of 3 questions about preference for the diagnosis and management of PTMC and 3 additional questions about respondents' personal information. An online survey was conducted from March 3 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The American Thyroid Association guidelines (2015 edition) recommend that non-invasive T1/T2 cN0 PTC does not require PCCND, and the 5-year survival rate of patients with active monitoring and active intervention is 98.2% (10). Park et al (25) conducted a questionnaire survey among patients with thyroid cancer after surgery and showed that 69.2% of patients with thyroid cancer approved of the operation with a low recurrence rate and could accept a slight amount of increased risk of complications. Chen et al (26) conducted a retrospective study of 18,376 PTC patients and showed PCCND could better remove potential lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The American Thyroid Association guidelines (2015 edition) recommend that non-invasive T1/T2 cN0 PTC does not require PCCND, and the 5-year survival rate of patients with active monitoring and active intervention is 98.2% (10). Park et al (25) conducted a questionnaire survey among patients with thyroid cancer after surgery and showed that 69.2% of patients with thyroid cancer approved of the operation with a low recurrence rate and could accept a slight amount of increased risk of complications. Chen et al (26) conducted a retrospective study of 18,376 PTC patients and showed PCCND could better remove potential lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological evaluation included various parameters likesample adequacy, background, cellular arrangement / pattern, cellular details including nuclear features [5]. A uniform reporting system for thyroid FNA will facilitate effective communication among cytopathologist, endocrinologist, radiologists and surgeons [15]. The Bethesda system of reporting thyroid cytopathology established a uniform tiered reporting system.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a self-administered questionnaire which was adapted from a prior study on comparable objectives [3].The questionnaire contains two sections. The first section gathers participants' personal information including age, gender, marital status, education level, monthly household income, and past medical history related to thyroid cancer surgery or history of thyroid cancer surgery.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…The American Thyroid Association's (ATA) new guidelines, as of 2015, advise FNA to be used only when nodules are larger than 1 cm in diameter, even in the presence of sonographic patterns that raise concern. Additionally, they endorse the recommendation of active observation for PTMCs as a viable substitute for immediate surgery [3]. The authors think it is crucial to use shared decision-making.…”
Section: Introductionmentioning
confidence: 97%